Kak pozhivaesh', Ufa? . Kak pozhivaesh', Ufa? . How Are You, Ufa? . Как поживаешь, Уфа? - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Negotiations with Moscow on the power and status of the Republic of Bashkortostan; the withdrawal of restrictions on accepting girls to study in the Higher School of the Ufa Russian Interior Ministry; the World Forum of Muslims; Pop Song Festival Agidel-92; Day of Older Persons. Contributors: Saitov, Azamat (Anchor) Переговоры с Москвой о полномочиях и статусе республики Башкортостан; о снятии ограничения на прием девушек на учебу в Уфимскую высшую школу МВД РФ; Всемирный форум мусульман; фестиваль эстрадной песни Агидель-92; День пожилых людей. Создатели: Саитов, Азамат (Ведущий/Ведущая)